Radiocarbon in global tropospheric carbon dioxide - Levin, Ingeborg; Hammer, Samuel; Kromer, Bernd; Preunkert, Susanne; Weller, Rolf; Worthy, Douglas E. (Radiocarbon, 2022)
Since the 1950s, observations of radiocarbon (14C) in tropospheric carbon dioxide (CO2) have been conducted in both hemispheres, documenting the so-called nuclear “bomb spike” and its transfer into the oceans and the terrestrial biosphere, the two compartments permanently exchanging carbon with the atmosphere. Results from the Heidelberg global network of Δ14C-CO2 observations are revisited here with respect to the insights and quantitative constraints they provided on these carbon exchange fluxes. The recent development of global and hemispheric trends of Δ14C-CO2 are further discussed in regard to their suitability to continue providing constraints for 14C-free fossil CO2 emission changes on the global and regional scale.
Erste Online-Veröffentlichung von Cambridge University Press: 23 December 2021
Gesehen am 24.06.2024